Buccal Cell Cytokeratin 14 Identifies Mild Cognitive Impairment and Alzheimer’ s Disease in the AIBL Study of Aging - R. Leifert, Wayne; Ferdoush Tuli, Jannatul; Francois, Maxime; Nguyen, Tori; Rembach, Alan; L. Rumble, Rebecca; Rainey-Smith, Stephanie; Martins, Ralph; F. Fenech, Michael; The Australian Imaging, Biomarkers; Lifestyle Study Research Group. (Current Alzheimer Research, 2015)
Previous studies have suggested that mild cognitive impairment (MCI) may be reflective of the early stages of neurodegenerative disorders such as Alzheimer’s disease (AD). The hypothesis was that cytokeratin (CK) 14 expression can be used as a biomarker in isolated buccal mucosa to identify individuals with MCI or AD from the Australian Imaging, Biomarkers and Lifestyle (AIBL) flagship study of aging. Visual assessment of buccal cell CK14 expression was carried out using immunofluorescence techniques. The frequency of basal buccal cells expressing CK14 was significantly lower in the MCI (P=0.0002) and AD (P<0.05) groups compared with the control group. Receiver-operating characteristic (ROC) curves were carried out for CK14 expression and yielded an area under the curve (AUC) of 0.899 for the MCI (P<0.0001) group and 0.772 for the AD (P=0.004) group. When the CK14 expression data were combined with plasma homocysteine concentration, the AUC was further improved to 0.932 and 0.788 for the MCI (P=0.0001) and AD (P=0.004) groups, respectively. APOE ε4 carriers in the control group had 21% lower CK14 expression compared with control non APOE ε4 carriers, however this difference was not statistically significant. The changes in the buccal cell CK14 expression observed in this pilot study could prove useful as a potential biomarker in identifying individuals with an increased risk of developing MCI and eventually AD. These promising results need to be replicated in a larger subset of the AIBL cohort and in cohorts of other neurodegenerative disorders to determine changes specific to AD.
Keywords: homocysteine